2022
DOI: 10.3389/fpsyg.2022.889503
|View full text |Cite
|
Sign up to set email alerts
|

Subjective wellbeing and psychological symptoms of university students during the COVID-19 pandemic: Results of a structured telephone interview in a large sample of university students

Abstract: University students are at elevated risk for psychological distress, especially during the COVID-19 pandemic. The aim of this study was to warmly contact our students and investigate the psychological impact of the COVID-19 pandemic on the subjective wellbeing (SWB) and levels of psychological symptoms (such as depressive and anxious feelings) of university students in Belgium. All bachelor and master students of the Vrije Universiteit Brussels (N = 15,475) were invited for a brief structured telephone intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…We discovered notable differences in Chinese university students' love forgiveness, interpersonal relationships, and subjective wellbeing between 2016 and 2023, the first hypothesis was valid. At first, compared with the period before the epidemic, undergraduates' subjective well-being decreased significantly after the epidemic, which corresponds with the findings in Baetens et al (2022) and Chen and Ye (2023). Krautter et al (2022) found that during the epidemic, the subjective well-being of college students obviously decreased.…”
Section: Theoretical Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…We discovered notable differences in Chinese university students' love forgiveness, interpersonal relationships, and subjective wellbeing between 2016 and 2023, the first hypothesis was valid. At first, compared with the period before the epidemic, undergraduates' subjective well-being decreased significantly after the epidemic, which corresponds with the findings in Baetens et al (2022) and Chen and Ye (2023). Krautter et al (2022) found that during the epidemic, the subjective well-being of college students obviously decreased.…”
Section: Theoretical Implicationssupporting
confidence: 83%
“…According to , undergraduates' subjective well-being in college during the epidemic period was at an above average level, which is consistent with the study results before the epidemic period. However, the study of Baetens et al (2022) shows the pandemic does adversely affect undergraduates' subjective well-being in college. Chen and Ye (2023) found that compared with the period before the epidemic, undergraduates' subjective well-being in college had decreased significantly during the COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…One study 15 from the SIGMA cohort reported a decrease and stabilization in psychopathological symptoms, measured with the Brief Symptom Inventory, and compared incidences in 2018, 2019 and 2020. Another Belgian study 16 with 7000 university students reported similar trends: Based on structured interviews based on the Kessler Psychological Distress scale (K6), the results show no significant increase in psychopathological symptoms during COVID-19 pandemic. These Belgian findings are not in line with other international studies and meta-analyses, where an increase in psychopathological symptoms during the COVID-19 pandemic is seen in adolescent samples.…”
Section: Introductionmentioning
confidence: 66%
“…Because of COVID‐19 the literature has revealed increased mental disorders (e.g., anxiety, depression, and loneliness) and serious consequences on the SWB of students (Besser et al, 2020; Huang & Zhang, 2021). In particular, students characterized by a lack of experience, uncertainty, and immature social networks seem more vulnerable to the threats of COVID‐19, closure of the campus, the shift from in‐person to online teaching, and limitations of interactions and social networks (Baetens et al, 2022; Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%